Influence Of Book Value Per Share, Net Income And Dividends To Merket Value Per Share On Manufacture Companies Listed In Indonesia Stock Exchange - Aulia Rahman Harahap (TRIGIN PUBLISHER, 2021)
This research has a purpose to determine the influence of book value per share, net income, and dividends to market value per share on manufacture companies listed on the Indonesia Stock Exchange (IDX). The hypothesis proposed: There is an influence of the book value per share, net income, and dividends on market value per share either partially or simultaneously. This research is classified as a causal research. Population used in this research were manufacturing company listed on the Indonesia Stock Exchange (IDX) in 2008- 2011 where the total population used is 120 manufacture companies. The sampling technique used was purposive sampling technique in which the number of samples obtained in this research were 19 companies. Data used in this research is secondary data. This research hypothesis are tested using multiple regression analysis with classical assumption test and goodness of fit to test the hypothesis. The results shows that either partially or simultaneously book value per share, net income, and dividends significantly influence the market value per share on manufacture companies listed on the Indonesia Stock Exchange (IDX). Adjusted R square value is 0,741 indicating that 74,1% change in stock market value can be explained by the independent variables used in this research. The remaining 25,9% is explained by other factors not included in the regression model.